Avaliação técnica e operacional da estação de tratamento de esgotos por lodos ativados do campus do Pici da Universidade Federal do Ceará - Peixoto, Marcelo Silva (2008)
Wastewater treatment is very important to maintain the quality of water bodies. The present work evaluated the technical and operational aspects of an activated sludge Wastewater Treatment Plant (WTP), classified as prolonged aeration, located at the “Campus do Pici” of the Federal University of Ceará, and propose some interventions to make compatible real and design efficiencies. The physical-chemical and biological water analysis of influent and effluent allowed to monitor the real WTP efficiency. Some operational parameters were assessed in the preliminary treatment, aeration tank and secondary settler. After the monitoring time, the real organic matter, nutrients and pathogens removal efficiencies were compared to values reported in literature for the activated sludge system in extended aeration, as well as for the operational parameters. Additionally, it was verified which parameters were below the limits reported in the regulation (Portaria no 154 of Secretaria de Meio ambiente do Ceará, Semace). It was concluded that the WTP was hydraulically overloaded, which is compromising the organic matter and pathogens removal, beside the low nutrients efficiency. Because of this, the WTP effluent is not accomplishing the regulation limits for ammonium and phosphorous. As a major intervention, we suggest the construction of other modules to distribute the inflow, with the aim of decrease the hydraulic overload problem, beside the possibility of including a tertiary treatment to decrease the nutrients concentrations. Only after these improvements we can think of ways to optimize the WTP to achieve the design efficiencies and effluent limits.